LARGE RETINAL PIGMENT EPITHELIAL RIP ASSOCIATED WITH BULLOUS RETINAL AND CHOROIDAL DETACHMENT. Issue Volume 11:Issues 4(2017:Autumn) (2017) - McCann, Jesse T.; Engelbert, Michael
Abstract : Purpose: To report a giant retinal pigment epithelium rip in a patient with a bullous retinal and choroidal detachment. Methods: Case report with widefield imaging, fundus autofluorescence, and optical coherence tomography of the retina. Results: This 62-year-old patient had a history of advanced glaucoma, trabeculectomy, blebitis, and endophthalmitis. He had cataract surgery 6 weeks before presentation. He was found to have a large bullous retinal and choroidal detachment with a large retinal pigment epithelium tear at the limit of the choroidal detachment. After vitrectomy for retinal detachment repair, the tear was observed to extend inferiorly at the margins of the choroidal detachment. Conclusion: This case report demonstrates that large retinal pigment epithelium rips can be found associated with large bullous choroidal and retinal detachments. These tears seem similar to tears that have been observed after trabeculectomy. Abstract : The authors have observed a patient with a bullous retinal and choroidal detachment with a large rip in the retinal pigment epithelium.